Parenting After A Natural Disaster - Donna Davis; Suzanna Smith (EDIS, 2006)
FAR-0001, a 2-page transcript of the radio broadcast by Donna Davis and Suzanna Smith, describes the impacts of stress from a natural disaster on family members and what parents can do to restore order to their family's life. Includes links to sounds files of the radio broadcast. Published by the UF Department of Family Youth and Community Sciences, August 2006.